Breast Milk Micronutrients and Child Health - Atajanova Shaira Khalilovna; Shakhobiddinova Nodirabegim Khabibullo kizi (Genius Journals, 2024)
The World Health Organization expresses concern about the problem of nutrition and micronutrient status of children and their mothers. Given that the nutrition of a nursing mother significantly affects the health of a newborn child through breast milk, increased attention should be paid to the nutrition of women of reproductive age. The article presents convincing data on the importance of individual microelements and vitamins for a growing child. The relevance of studying the micronutrient status of nursing mothers and infants is emphasized.
Keywords: breastfeeding; vitamin D; infant; micronutrients